2018
DOI: 10.1039/c7em00470b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the hydraulic fracturing parameter space: a novel high-pressure, high-throughput reactor system for investigating subsurface chemical transformations

Abstract: Hydraulic fracturing coupled with horizontal drilling (HDHF) involves the deep-well injection of a fracturing fluid composed of diverse and numerous chemical additives designed to facilitate the release and collection of natural gas from shale plays. Analyses of flowback wastewaters have revealed organic contamination from both geogenic and anthropogenic sources. The additional detections of undisclosed halogenated chemicals suggest unintended in situ transformation of reactive additives, but the formation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 25 publications
4
45
0
Order By: Relevance
“…Although the role of halogen radicals in the degradation and halogenation of additives in hydraulic fracturing fluids has not yet been investigated, there are two primary reasons to suspect that they may be involved in these reactions. First, hydraulic fracturing fluids frequently have even higher halide concentrations (e.g., median Cl – and Br – concentrations of up to 4.6 M and 5.0 mM, respectively) than seawater or brines previously shown to be conducive to halogen radical formation. ,,, Second, oxidative breakers (e.g., persulfate, S 2 O 8 2– ) are widely used to generate radicals (in particular, sulfate radical) at high temperatures (i.e., 40–100 °C) to break down polymer gels (i.e., guar). , The use of persulfate as an oxidative breaker is associated with the formation of halogenated products in hydraulic fracturing fluids, and water treatment with sulfate radical in the presence of halides can lead to the halogenation of organic compounds. Notably, sulfate radical generated from thermally activated persulfate is likely to generate halogen radicals because it can be scavenged directly by either Cl – or Br – (eqs and , ). In comparison, halogen radical formation from hydroxyl radicals is limited by the rapid reverse reaction of the intermediate ClOH •– (eq ), which limits its accumulation .…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of halogen radicals in the degradation and halogenation of additives in hydraulic fracturing fluids has not yet been investigated, there are two primary reasons to suspect that they may be involved in these reactions. First, hydraulic fracturing fluids frequently have even higher halide concentrations (e.g., median Cl – and Br – concentrations of up to 4.6 M and 5.0 mM, respectively) than seawater or brines previously shown to be conducive to halogen radical formation. ,,, Second, oxidative breakers (e.g., persulfate, S 2 O 8 2– ) are widely used to generate radicals (in particular, sulfate radical) at high temperatures (i.e., 40–100 °C) to break down polymer gels (i.e., guar). , The use of persulfate as an oxidative breaker is associated with the formation of halogenated products in hydraulic fracturing fluids, and water treatment with sulfate radical in the presence of halides can lead to the halogenation of organic compounds. Notably, sulfate radical generated from thermally activated persulfate is likely to generate halogen radicals because it can be scavenged directly by either Cl – or Br – (eqs and , ). In comparison, halogen radical formation from hydroxyl radicals is limited by the rapid reverse reaction of the intermediate ClOH •– (eq ), which limits its accumulation .…”
Section: Introductionmentioning
confidence: 99%
“…(Luek et al, 2018). Formation of halogenated compounds of common fracking additives (cinnamaldehyde, epichlorohydrin and 2,2-dibromo-3-nitrilopropionamide) has been experimentally confirmed under simulated conditions of high pressure, high temperature, presence of oxidizing agents (ammonium persulfate) and salinity (Sumner and Plata, 2018). These halogenated compounds may need further monitoring as they are likely to be recalcitrant to biodegradation and pose health risks.…”
Section: Transformation Productsmentioning
confidence: 95%
“…During hydraulic fracturing operations, the mixture of water and chemical additives that comprise HFF is in contact with the target shale formation for weeks and reacts with the brine and shale in the formation at high temperature and pressure. During this time, numerous interactions can take place that significantly alter HFF fluid chemistry, the mineral composition and petrophysical properties of shale, and the release of organic and inorganic contaminants (Hoelzer et al, 2016;Harrison et al, 2017;Paukert Vankeuren et al, 2017;Sumner and Plata, 2018aPilewski et al, 2019;Hakala et al, 2021). Studies conducted using benchtop reactors showed that multiple shale-HFF reactions could occur, such as mineral precipitation and dissolution, organo-metallic complex formation, ion adsorption onto shale organic matter and clay minerals, and organic matter degradation (Jew et al, 2017;Sumner and Plata, 2018a;Pilewski et al, 2019;Hakala et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…During this time, numerous interactions can take place that significantly alter HFF fluid chemistry, the mineral composition and petrophysical properties of shale, and the release of organic and inorganic contaminants (Hoelzer et al, 2016;Harrison et al, 2017;Paukert Vankeuren et al, 2017;Sumner and Plata, 2018aPilewski et al, 2019;Hakala et al, 2021). Studies conducted using benchtop reactors showed that multiple shale-HFF reactions could occur, such as mineral precipitation and dissolution, organo-metallic complex formation, ion adsorption onto shale organic matter and clay minerals, and organic matter degradation (Jew et al, 2017;Sumner and Plata, 2018a;Pilewski et al, 2019;Hakala et al, 2021). Among these, mineral dissolution and precipitation reactions impact the porosity and permeability of shale the most.…”
Section: Introductionmentioning
confidence: 99%